A Physiologically‐Based Quantitative Systems Pharmacology Model of the Incretin Hormones GLP‐1 and GIP and the DPP4 Inhibitor Sitagliptin - Pavel Balazki; Stephan Schaller; Thomas Eissing; Thorsten Lehr (Wiley, 2020)
Incretin hormones glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) play a major role in regulation of postprandial glucose and the development of type 2 diabetes mellitus. The incretins are rapidly metabolized, primarily by the enzyme dipeptidyl‐peptidase 4 (DPP4), and the neutral endopeptidase (NEP), although the exact metabolization pathways are unknown. We developed a physiologically‐based (PB) quantitative systems pharmacology model of GLP‐1 and GIP and their metabolites that describes the secretion of the incretins in response to intraduodenal glucose infusions and their degradation by DPP4 and NEP. The model describes the observed data and suggests that NEP significantly contributes to the metabolization of GLP‐1, and the traditional assays for the total GLP‐1 and GIP forms measure yet unknown entities produced by NEP. We further extended the model with a PB pharmacokinetics/pharmacodynamics model of the DPP4 inhibitor sitagliptin that allows predictions of the effects of this medication class on incretin concentrations.